Genetic variation in parthenogenetic Caucasian rock lizards of the genus Lacerta (L. dahli, L. armeniaca, L. unisexualis) analyzed by DNA fingerprinting - Tokarskaya, O.; Kan, N.; Petrosyan, V.; Martirosyan, I.; Grechko, V.; Danielyan, F.; Darevsky, I.; Ryskov, A. (Molecular genetics and genomics : MGG, 2001)
Multilocus DNA fingerprinting has been used to study the variability of some mini- and microsatellite sequences in parthenogenetic species of Caucasian rock lizards of the genus Lacerta (L. dahli, L. armeniaca and L. unisexualis). We demonstrate that these clonally reproducing lizards possess species-specific DNA fingerprints with a low degree of intra- and interpopulation variation. Mean indices of similarity obtained using M13 DNA, (GACA)4 and (TCC)50 as probes were 0.962 and 0.966 in L. dahli and L. armeniaca, respectively. The mean index of similarity obtained using M 13 and GATA probes in L. unisexualis was estimated to be 0.95. However, despite the high degree of band-sharing, variable DNA fragments were revealed in all populations with the microsatellite probes. An particularly high level of variability was observed for (TCC)n microsatellites in populations of L. unisexualis. In fact TCC-derived DNA fingerprints were close to being individual-specific, with a mean index of similarity of 0.824. Fingerprint analysis of parthenogenetic families of L. armeniaca showed that all maternal fragments were inherited together by the progeny, and no differences in fingerprint patterns were observed. On the other hand, while identical DNA fingerprints were obtained from L. unisexualis families with M13 and (GATA)4 probes, use of the (TCC)50 probe revealed remarkable intrafamily variation in this species. It is assumed that the genetic heterogeneity observed in parthenogenetic populations may be explained, at least in part, by the existence of genetically unstable microsatellite loci. Our data serve to illustrate processes of spontaneous mutagenesis and the initial stages of clonal differentiation in natural populations of the lizard species studied.